Exploring biomarkers of age in routine diagnostics for the risk stratification of older patients in the emergency department. (14th October 2021) - Bahrmann, P; Kunz, A L; Schoenstein, A; Giannitsis, E; Wahl, H.-W; Katus, H; Frey, N; Bahrmann, A
Abstract: Objectives: To estimate the association of the routinely applied biological age-related biomarkers hs-TnT, CRP and Hemoglobin (Hb) with mortality for the purpose of older patient's risk stratification in the emergency department (ED). Design: Exploratory, prospective cohort study with a follow-up at 2.5 years after recruitment start. Setting and participants: A cardiological emergency department (ED), chest pain unit, of our University Hospital. N=256 cardiological ED patients with a minimum age of 70 years and with an expected life-expectancy above 24h. Methods: Data from the hospital files were supplemented by a questionnaire. Patients were followed-up for mortality by requesting registry office information. Results: Among N=256 patients 63 died over the follow-up period. Positive results in each of the three biomarkers alone as well as the combination were associated with increased all-cause mortality at follow-up. The number of positive age-related biomarkers appeared to be strongly indicative of the risk of mortality, even when controlled for major confounders (age, sex, BMI, creatinine clearance, and comorbidity). Conclusion and implications: In older ED patients, biomarkers explicitly related to biological aging processes such as hs-TnT, CRP and Hb were independently of each other as well as combined associated with an increased risk of all-cause mortality. Thus, they may have the potential to be used to supplement the general risk stratification of older patients in the ED. Validation of the results in a large dataset is needed. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Robert Bosch Foundation, Stuttgart, Germany